A Novel Arthroscopic Classification of Degenerative Medial Meniscus Posterior Root Tears Based on the Tear Gap - Kim, Jae-Young (Orthop J Sports Med, 2019)
BACKGROUND: Degenerative medial meniscus posterior root tears (MMPRTs) are reportedly associated with medial compartment osteoarthritis and meniscal extrusion with a displaced gap from the root insertion. However, degenerative MMPRTs have not yet been clearly classified according to arthroscopic findings. PURPOSE: To classify degenerative MMPRTs according to the tear gap and to investigate how the classification could reflect the joint condition properly. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: Patients who underwent arthroscopic surgery, performed by a single orthopaedic surgeon, for degenerative MMPRTs between August 2006 and February 2017 were included. MMPRTs were classified according to tear patterns observed during arthroscopic surgery (type 1, incomplete root tear; types 2-5, complete root tears), with each type further divided by the size of the tear gap, defined as the degree of tear displacement from the root (type 2, no gap or overlapped; type 3, gap of 1-3 mm; type 4, gap of 4-6 mm; type 5, gap of ≥7 mm). We compared preoperative factors, including the Kellgren-Lawrence (K-L) grade, absolute extrusion, relative percentage of extrusion (RPE), tear gap on magnetic resonance imaging (MRI), and mechanical alignment, as well as intraoperative factors, including chondral wear at surgery, between each MMPRT type. RESULTS: A total of 116 root tears were categorized according to this classification: type 1, 16.4% (19 knees); type 2, 9.5% (11 knees); type 3, 40.5% (47 knees); type 4, 25.0% (29 knees); and type 5, 8.6% (10 knees). Chondral wear of the medial femoral condyle (MFC) (P = .001), K-L grade (P = .001), meniscal extrusion (P = .001), and tear gap on MRI (P = .001) showed a tendency to increase with a higher tear type. Chondral wear (ρ for MFC = 0.388; ρ for MTP = 0.311), K-L grade (ρ = 0.390), and meniscal extrusion (ρ for absolute extrusion = 0.500; ρ for RPE = 0.451) showed a moderate correlation with tear type, whereas tear gap on MRI (ρ = 0.907) showed a strong correlation with tear type. CONCLUSION: Our study introduces a new classification based on the tear gap that can concisely describe a degenerative MMPRT. The classification system demonstrated that a higher tear type (increasing displacement of the tear gap in arthroscopic surgery) is associated with higher meniscal extrusion, severe chondral wear, and greater severity of arthritis.